Estimating carbon and water footprints associated with commercial milk formula production and use: development and implications of the Green Feeding Climate Action Tool - Smith, Julie P.; Borg, Bindi; Nguyen, Tuan T.; Iellamo, Alessandro; Pramono, Andini; Mathisen, Roger (Frontiers in Nutrition, 2024)
Carbon offset frameworks like the UN Clean Development Mechanism (CDM) have largely overlooked interventions involving food, health, and care systems, including breastfeeding. The innovative Green Feeding Climate Action Tool (GFT) assesses the environmental impact of commercial milk formula (CMF) use, and advocates for breastfeeding support interventions as legitimate carbon offsets. This paper provides an overview of the GFT’s development, key features, and potential uses. The offline and online GFT were developed using the DMADV methodology (Define, Measure, Analyze, Design, Verify). The GFT reveals that the production and use of CMF by infants under 6 months results in annual global greenhouse gas (GHG) emissions of between 5.9 and 7.5 billion kg CO2 eq. and consumes 2,562.5 billion liters of water. As a national example, in India, one of the world’s most populous countries, CMF consumption requires 250.6 billion liters of water and results in GHG emissions ranging from 579 to 737 million kg CO2 eq. annually, despite the country’s high breastfeeding prevalence among infants under 6 months. The GFT mainly draws on data for low- and middle-income countries (LMICs), as many high-income countries (HICs) do not collect suitable data for such calculations. Despite poor official data on breastfeeding practices in HICs, GFT users can input their own data from smaller-scale surveys or their best estimates. The GFT also offers the capability to estimate and compare baseline with counterfactual scenarios, such as for interventions or policy changes that improve breastfeeding practices. In conclusion, the GFT is an important innovation to quantify CMF’s environmental impact and highlight the significance of breastfeeding for planetary as well as human health. Women’s contributions to environmental preservation through breastfeeding should be recognized, and breastfeeding interventions and policies should be funded as legitimate carbon offsets. The GFT quantifies CMF’s carbon and water footprints and facilitates financing breastfeeding support as a carbon offset initiative under CDM funding facilities.